Penerapan Prinsip-Prinsip Dasar Konsolidasi Laporan Keuangan Pada Perusahaan Grup di Indonesia: Studi Perbandingan antara PSAK dan IFRS - Raditya Rabert Priatna; Fahri Fakhturohman; M. Masrukhan (Politeknik Kampar, 2024)
This study examines the implementation of the fundamental principles of financial statement consolidation in group companies in Indonesia, by analyzing the sample of PT Indofood Sukses Makmur Tbk. This research focuses on applying the basic principles of consolidation in related companies and a comparative study between Statement of Financial Accounting Standards (PSAK) 65 and International Financial Reporting Standards (IFRS) 10. PSAK 65 is designed to meet regulatory needs in Indonesia, while IFRS 10 offers an internationally applicable financial reporting framework. The research method uses a qualitative approach with descriptive analysis based on related literature data and company financial reports. The research findings found that PT Indofood has applied the consolidation principle in accordance with PSAK 65, including the management of assets, liabilities, equity, and disclosure of subsidiaries. The findings highlight the importance of adopting global accounting standards to improve transparency and comparability of financial statements, while taking into account local customizations. This research provides insight into the challenges and benefits of accounting standards convergence in Indonesia.